Seismic strengthening of conventional timber structures using resilient braces. (August 2021) - Hashemi, Ashkan; Yousef-Beik, Seyed Mohammad Mahdi; Zarnani, Pouyan; Quenneville, Pierre
Abstract: The observations from recent seismic events, shake table tests and large-scale experimental studies showed that mass timber structures demonstrate acceptable seismic performance. For these structures, the connectors are designed to demonstrate a ductile behaviour during the earthquake which is accompanied by inelastic deformation of the fasteners and crushing of the wood fibres. Despite the observed satisfactory seismic performance, the significant lateral stiffness degradation, as a result of irrecoverable damage in the connectors, makes these structures vulnerable to aftershocks and future events. Nowadays, a low damage seismic performance where the damage is localised in the replicable fuse and the inter-story drifts are capped within the desired range may be the preferred performance criteria for new timber buildings. This paper aims to assess the seismic performance of conventional mass timber buildings upgraded with resilient low damage braces. A design procedure for the strengthening of the lateral load resisting system is proposed and applied to a case study structure. The results showed that while the original structure failed to meet the defined seismic performance criteria, the strengthened structure demonstrated superior seismic performance. Furthermore, the lateral performance of the original and strengthened systems under subsequent earthquakes is investigated. The results of this study show the significant potential of the introduced bracing system for the strengthening of mass timber structures.